Real-world bleeding in patients with acute coronary syndrome (ACS) undergoing percutaneous coronary intervention (PCI) and prescribed different combinations of dual antiplatelet therapy (DAPT) in England: a population-based cohort study emulating a ‘target trial’ - Pufulete, M; Harris, J; Pouwels, KB; Reeves, BC; Lasserson, D; Loke, YK; Mumford, A; Mahadevan, K; Johnson, TW (BMJ Publishing Group, 2022)
Objective To estimate the incidence and HRs for bleeding for different dual antiplatelet therapies (DAPT) in a real-world population with acute coronary syndrome (ACS) undergoing percutaneous coronary intervention (PCI) in England.